2003
DOI: 10.1167/iovs.02-0198
|View full text |Cite
|
Sign up to set email alerts
|

Support of Retinal Ganglion Cell Survival and Axon Regeneration by Lithium through a Bcl-2-Dependent Mechanism

Abstract: Lithium supports both the survival and regeneration of RGC axons through a Bcl-2-dependent mechanism. This suggests that lithium may be used to treat glaucoma, optic nerve neuritis, the degeneration of RGCs and their nerve fibers, and other brain and spinal cord disorders involving nerve damage and neuronal cell loss. To achieve full regeneration of the severed optic nerve, it may be essential to combine lithium therapy with other drugs that mediate induction of a permissive environment in the mature central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 42 publications
4
65
0
1
Order By: Relevance
“…It has been reported that Bcl-2 protects neurons from apoptotic cell death as well as enhances axonal regeneration after CNS injury (Chen et al, 1997;Yukawa et al, 2002;Huang et al, 2003). Here we have sought to ex-LITHIUM AND CHONDROITINASE ABC PROMOTE REGENERATION amine whether LiCl treatment enhances the expression of Bcl-2 in RST neurons after injury of the spinal cord.…”
Section: Expression Of Bcl-2 After Licl Treatmentmentioning
confidence: 97%
“…It has been reported that Bcl-2 protects neurons from apoptotic cell death as well as enhances axonal regeneration after CNS injury (Chen et al, 1997;Yukawa et al, 2002;Huang et al, 2003). Here we have sought to ex-LITHIUM AND CHONDROITINASE ABC PROMOTE REGENERATION amine whether LiCl treatment enhances the expression of Bcl-2 in RST neurons after injury of the spinal cord.…”
Section: Expression Of Bcl-2 After Licl Treatmentmentioning
confidence: 97%
“…41 In brief, retinas taken from postnatal day 2 (P2) mouse pups (n ϭ 4 per group) were dissected and dissociated by incubation with 1% papain (Worthington Biochemical, Lakewood, NJ) in Hank's buffered saline solution containing 5 U/mL DNase (Gibco; Invitrogen) for 10 minutes at 37°C. Dissociated cells were transferred to a solution containing the papain inhibitor ovomucoid (1%; Worthington Biochemical) and were triturated.…”
Section: Examination Of Ngb Function In Purified Rgc Culturesmentioning
confidence: 99%
“…32,45 We therefore hypothesized that, if NGB acts cell autonomously as a neuroprotective protein under ocular hypertension in vivo, we would observe a neuroprotective effect of NGB against glutamate-induced neurotoxicity in purified RGC cultures. RGCs were isolated from P2 WT and Ngb-Tg mouse pups as described previously 41 and were cultured under various concentrations of glutamate. As expected, increasing levels of glutamate stimulation resulted in incremental loss of RGCs in culture.…”
Section: Neuroprotective Effect Of Ngb In Purified Rgc Culturesmentioning
confidence: 99%
“…Investigators have therefore postulated that a prerequisite for successful regeneration of severed optic nerves in adult mammals is the activation of an intrinsic regenerative mechanism of RGC axons, namely the induction of bcl-2 expression in neurons. Studies were therefore undertaken to determine whether lithium would not only prevent injury-induced degeneration of RGCs and other CNS neurons but also promote the regeneration of their axons (Huang et al 2003). These studies showed that lithium, acting directly on RGCs, supports both neuronal survival and axon regeneration at its established therapeutic concentrations (.5-1.2 mmol/L) (Huang et al 2003).…”
Section: Lithium Exerts Not Only Protective But Also Regenerative Effmentioning
confidence: 99%
“…Studies were therefore undertaken to determine whether lithium would not only prevent injury-induced degeneration of RGCs and other CNS neurons but also promote the regeneration of their axons (Huang et al 2003). These studies showed that lithium, acting directly on RGCs, supports both neuronal survival and axon regeneration at its established therapeutic concentrations (.5-1.2 mmol/L) (Huang et al 2003).…”
Section: Lithium Exerts Not Only Protective But Also Regenerative Effmentioning
confidence: 99%